Uncovering the Synergy: Karnataka Government's Collaboration with Third Sector Organizations (TSOs) for Rural Development and Support during Covid-19 - Bharathi, T. N., M.S. Ganapathy; Siddayya; Sree Lakshmi, A. (Archives of Current Research International, 2024)
Aims: Third sector organisations comprises of charities, social enterprises, and voluntary groups supporting communities at local level. The study has focused on the relationship between the State and Third Sector Organizations (TSOs) in delivering services to impoverished rural community. Study Design: Mention the design of the study here. Place and Duration of Study: Thirty TSOs were chosen from Kolar, Chikkaballapur, and Tumakuru districts, encompassing a variety of entities including NGOs, SHGs, and primary-level cooperatives, which collectively constitute the third sector comprising charities, social enterprises, and voluntary groups supporting local communities. The data pertains to the year 2021-22. Methodology: To achieve the specific objectives of the study, descriptive statistics were employed to assess the service delivery dynamics between the State and TSOs. Results: The findings revealed that during the unprecedented times of the COVID-19 pandemic, Third Sector Organizations (TSOs) have played a crucial role in extending support to communities in various spheres. Despite the challenges posed by the pandemic, TSOs extended educational support to 1,687 individuals, representing 2.06 per cent of the total beneficiaries. A significant majority (83.33%) of these organisations actively participated in implementation of Government-supported projects, maintaining a two-way relationship with the government (73.33%). The organisations had also taken financial help from Government in the form of funds (70 %), grants (33.33 %), and subsidies (33.33 %). The study also revealed that majority (66.67 %) of the organizations were having political interference in TSO. Furthermore, a substantial majority (90%) of the organizations anticipated timely financial support from the Government. Conclusion: The study underscores the indispensable role of Third Sector Organizations (TSOs) in bolstering impoverished rural communities, particularly during the COVID-19 pandemic. Despite challenges, TSOs actively engage in government-supported projects, fostering a symbiotic relationship. However, concerns persist regarding political interference within TSOs, highlighting the need for safeguarding their autonomy. Overall, the findings emphasize the necessity of consistent and timely financial support from the government to sustain TSO initiatives effectively. The study recommended the necessity of providing punctual financial support from the government to encourage TSOs in enhancing their service delivery to the rural poor.